Numerical Solution of Second Order Delay Type Differential equation by Collocation Method via First Boubeker Polynomials - Bilal, Muhammad; Norhayati, Rosli; Ahmad, Iftikhar; Ullah, Safi (Research India Publications, 2017)
In this paper a numerical method has been applied to solve second order pantograph differential equations via Boubeker polynomial. To examine the validity and convergence of the proposed method, we presented some test problems of second order Pantograph differential equations. Moreover, results obtained through the proposed technique are in comparison with the reported results and it was found good in agreement.